Pendampingan dan Penerapan Strategi Digital Marketing UMKM Spikoe Jadoel di Kelurahan Rungkut Kidul - Alvian Priambudi; Riko Setya Wijaya; M. Taufiq (Yayasan Daarul Huda Kruengmane, 2023)
This research is a type of descriptive research with a qualitative approach. Researchers used data collection techniques in the form of interviews with UMKM partners